Comparison of SARS-CoV-2 sequencing using the ONT GridION and the Illumina MiSeq - Derek Tshiabuila; Jennifer Giandhari; Sureshnee Pillay; Upasana Ramphal; Yajna Ramphal; Arisha Maharaj; Ugochukwu Jacob Anyaneji; Yeshnee Naidoo; Houriiyah Tegally; Emmanuel James San; Eduan Wilkinson; Richard J. Lessells; et al. (BMC Genomics, 2022)
Abstract Background Over 4 million SARS-CoV-2 genomes have been sequenced globally in the past 2 years. This has been crucial in elucidating transmission chains within communities, the development of new diagnostic methods, vaccines, and antivirals. Although several sequencing technologies have been employed, Illumina and Oxford Nanopore remain the two most commonly used platforms. The sequence quality between these two platforms warrants a comparison of the genomes produced by the two technologies. Here, we compared the SARS-CoV-2 consensus genomes obtained from the Oxford Nanopore Technology GridION and the Illumina MiSeq for 28 sequencing runs. Results Our results show that the MiSeq had a significantly higher number of consensus genomes classified by Nextclade as good and mediocre compared to the GridION. The MiSeq also had a significantly higher genome coverage and mutation counts than the GridION. Conclusion Due to the low genome coverage, high number of indels, and sensitivity to SARS-CoV-2 viral load noted with the GridION when compared to MiSeq, we can conclude that the MiSeq is more favourable for SARS-CoV-2 genomic surveillance, as successful genomic surveillance is dependent on high quality, near-whole consensus genomes.